Effects of school sports spaces on electromyography activity of lower limb and erector spinae muscles during running in students - Azizian, N.; Abdollahpour Darvishani, M.; Jafarnezhadgero, A.; Dehghani, M.; Momenifar, F. (Journal of Advanced Sport Technology, 2020)
The aim of this study was to evaluate the effects of school sport spaces on electromyography activity of lower limb and erector spinae muscles during running in students.Fifteen students with an age range between 10 to 14 years from schools with suitable sport facilities and fifteen students with the same age range from schools with inappropriate sport spaces. A wireless electromyography system with 8 pairs of bipolar surface electrodes (sample rate: 2000 Hz) was used to record the electromyography activity of back and lower limb muscles during running. The results showed that during the loading response phase, median frequency of the tibialis anterior (p=0.005, d=1.27) and medial gastrocnemius (p=0.021, d=0.93) muscles in the suitable sport facilities group were higher than that the other group by 13.45% and 38.28%, respectively. Also, during the propulsion phase, median frequency of biceps femoris muscle in the suitable sport facilities group was higher than that the other group by 28.88% (p=0.002, d=1.37). In addition, during the loading response phase, amplitude of medial gastrocnemius (p=0.024, d=0.84) and erector spinae (p=0.014, d=0.85) muscles in the suitable sport facilities group were lower than other group by 35.55% and 43.29%, respectively. The results of this study showed that students in schools with suitable sport facilities have better performance of the lower limb and erector spinae muscles while running, which reduces the chance of injury during running.